Penyediaan Pendidik dan Tenaga Kependidikan dalam Pendidikan Islam - Siti Hadiyanti Dini Islamiati; Iswan; Ahmad Suryadi Nomi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Islamic education aims to develop individual potential as a whole, including spiritual, intellectual, emotional and physical aspects, in accordance with Islamic values ​​and principles. Therefore, qualified educators and educational staff are needed. This qualitative research uses a library research method, namely a research method carried out by observing various literature related to the problems in the research, in the form of papers, books or writings, both from print and online media. The results of this research are that the quality of educators and educational staff in Islamic educational institutions is currently still a complex and challenging issue. Even though there are efforts to improve quality standards, there are still various challenges that need to be overcome, such as lack of qualifications and competence of educators, low welfare, minimal training and professional development, and inadequate policy support. To overcome this challenge, collaboration is needed between the government, educational institutions and communities to implement structured training and development programs and improve the welfare of educators.